已知函数 f(x)=cos(2x- π 3 )+2sin(x- π 4 )sin(x+ π 4 ) .

1个回答

  • (1)∵ f(x)=cos(2x-

    π

    3 )+2sin(x-

    π

    4 )sin(x+

    π

    4 )

    =

    1

    2 cos2x+

    3

    2 sin2x+(sinx-cosx)(sinx+cosx)

    =

    1

    2 cos2x+

    3

    2 sin2x+si n 2 x-co s 2 x =

    1

    2 cos2x+

    3

    2 sin2x-cos2x

    = sin(2x-

    π

    6 )

    ∴周期T=

    2 =π

    由 2x-

    π

    6 =kπ+

    π

    2 (k∈Z),得x=

    2 +

    π

    3 (k∈Z)

    ∴函数图象的对称轴方程为 x=kπ+

    π

    3 (k∈Z)

    (2)∵ x∈[-

    π

    12 ,

    π

    2 ] ,∴ 2x-

    π

    6 ∈[-

    π

    3 ,

    6 ] ,

    因为 f(x)=sin(2x-

    π

    6 ) 在区间 [-

    π

    12 ,

    π

    3 ] 上单调递增,在区间 [

    π

    3 ,

    π

    2 ] 上单调递减,

    所以当 x=

    π

    3 时,f(x)取最大值1,

    又∵ f(-

    π

    12 )=-

    3

    2 <f(

    π

    2 )=

    1

    2 ,当 x=-

    π

    12 时,f(x)取最小值 -

    3

    2 ,

    所以函数f(x)在区间 [-

    π

    12 ,

    π

    2 ] 上的值域为 [-

    3

    2 ,1] .